2011
DOI: 10.1056/nejmoa1005565
|View full text |Cite
|
Sign up to set email alerts
|

A Hemodynamic Study of Pulmonary Hypertension in Sickle Cell Disease

Abstract: In this study of adults with sickle cell disease, the prevalence of pulmonary hypertension as confirmed on right heart catheterization was 6%. Echocardiographic evaluation alone had a low positive predictive value for pulmonary hypertension. (Funded by the French Ministry of Health and Assistance Publique-Hôpitaux de Paris; ClinicalTrials.gov number, NCT00434902.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
498
1
14

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(544 citation statements)
references
References 27 publications
31
498
1
14
Order By: Relevance
“…Sickle cell patients with leg ulcers constitute a relatively distinct sub-phenotype, characterized by less frequent hospitalizations for vaso-occlusive pain crisis [22,23], while they are prone to develop pulmonary hypertension [5,[24][25][26][27][28], suggesting that the two complications share a common pathophysiology. In a cohort of 20 SCD patients with leg ulcer who underwent right hearth catheterization for suspected pulmonary hypertension, 15 had confirmation of PAH (personal data, this cohort has been described in Mehari et al (2013) [24].…”
Section: Epidemiologymentioning
confidence: 99%
“…Sickle cell patients with leg ulcers constitute a relatively distinct sub-phenotype, characterized by less frequent hospitalizations for vaso-occlusive pain crisis [22,23], while they are prone to develop pulmonary hypertension [5,[24][25][26][27][28], suggesting that the two complications share a common pathophysiology. In a cohort of 20 SCD patients with leg ulcer who underwent right hearth catheterization for suspected pulmonary hypertension, 15 had confirmation of PAH (personal data, this cohort has been described in Mehari et al (2013) [24].…”
Section: Epidemiologymentioning
confidence: 99%
“…The prevalence of elevated TRV using echocardiography is estimated to be 25-30% among SCA patients and 10-25% in those with genotype SC 6,8,11 . However, studies have reported that only about 6-11% of patients with TRV ≥ 2.5m/s on ECHO have confirmed pulmonary hypertension on right heart catheterization 12,13 . Notwithstanding, elevated TRV ≥ 2.5m/s in sickle cell patients has been significantly associated with decreased exercise tolerance and increased mortality estimated to be about 40% at 40 months of follow-up and is therefore considered an independent risk factor for death among these patients 6,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Age, sex, and distribution of hemoglobinopathies of our patients are similar to those of other published cohorts. 3,4 The hemodynamic profile reveals elevated right atrial pressures and mean pulmonary arterial pressure (mPAP), with relatively higher cardiac outputs and lesser elevation in pulmonary vascular resistance (PVR), as typically seen in SCDPH. However, notably, the average cardiac output was lower than that of other cohorts, with or without PH.…”
mentioning
confidence: 99%
“…Nargues A. Weir, 1 Rehan Saiyed, 2 Shoaib Alam, 1 Anna Conrey, 2 Himanshu D. Desai, 3 M. Patricia George, 4 Jennifer H. Keeley, 4 Elizabeth S. Klings, 5 Alem Mehari,6 James G. Taylor VI, 2 …”
mentioning
confidence: 99%